1993
DOI: 10.1002/1097-0142(19930201)71:3<820::aid-cncr2820710326>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Paragangliomas. Static cytometric studies of nuclear DNA patterns

Abstract: Background. The biologic behavior of most paragangliomas cannot be predicted from their histologic appearance. Recently, cytometric studies have found an association between an aggressive clinical behavior and the presence of a hyperdiploid or tetraploid range in the DNA nuclear content. Methods. The authors have studied morphometric (nuclear area and nuclear form factor) and DNA densitometric (integral optical density and DNA ploidy) features of 23 cases of paraganglioma by means of slide cytophotometry with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…However, paragangliomas are extremely well vascularized and central hypovascularity or necrosis seldom is observed. To our knowledge DNA ploidy studies and immunohistochemistry of paragangliomas to date have shown that these tumors are heterogeneous in DNA ploidy and expression of different proliferation markers 19–21. This heterogeneity could reflect differences in growth rate, but to our knowledge this has yet to be investigated.…”
Section: Discussionmentioning
confidence: 96%
“…However, paragangliomas are extremely well vascularized and central hypovascularity or necrosis seldom is observed. To our knowledge DNA ploidy studies and immunohistochemistry of paragangliomas to date have shown that these tumors are heterogeneous in DNA ploidy and expression of different proliferation markers 19–21. This heterogeneity could reflect differences in growth rate, but to our knowledge this has yet to be investigated.…”
Section: Discussionmentioning
confidence: 96%
“…External diploid controls were used to determine DNA indices (complete rat hepatocytes and lymphocytes from reactive lymph nodes) and to standardize the nuclear area/DNA content analysis (basal keratinocytes from normal areas) 23,24 . The internal controls were used for setting the G 0 /G 1 cell limits and calculating the DNA index of each G 0 /G 1 peak (> 10% of measured cells with evidence of G 2 + M cells) 25–27 .…”
Section: Methodsmentioning
confidence: 99%
“…The utility of DNA ploidy analysis in the assessment of prognosis is limited because of the presence of aneuploid or tetraploid DNA patterns in more than 50% of clinically benign lesions and the inability of a diploid pattern to exclude malignant behavior (6,7). Clearly reliable prognostic markers for the prediction of clinical outcome in PHEOs are needed to assign optimal treatment for malignant tumors.…”
mentioning
confidence: 99%